Guardians of privacy in the age of artificial intelligence: Librarians’ roles and realities in the Fourth Industrial Revolution: A case study involving two academic libraries in Cape Town - Ocks, Yumnaa; Salubi, Oghenere G. (South African Journal of Information Management, 2026)
Background: The Fourth Industrial Revolution (4IR) has introduced transformative technologies into academic libraries, offering opportunities to enhance access, efficiency and service delivery. The increasing reliance on digital platforms, data-driven tools and third-party services raises challenges regarding privacy, data protection and ethical information management. Objectives: This study was guided by two research objectives. Firstly, it sought to investigate the current and projected adoption of 4IR technologies in academic libraries to enhance service provision. Secondly, it aimed to examine academic librarians’ concerns regarding user privacy within these evolving technological practices. Method: Drawing on a case study of two academic libraries in Cape Town, this study examines librarians’ awareness, perceptions, and practices concerning data privacy, cybersecurity and regulatory compliance with the Protection of Personal Information Act. Using a qualitative case study of two anonymised academic libraries in Cape Town, the study examined librarians’ awareness, perceptions and practices regarding data privacy, cybersecurity and compliance with the POPI Act. The study also used thematic analysis to interpret the data and to provide insight into how institutional policies and technological infrastructures shape librarians’ responses to data protection obligations. Furthermore, the study highlights emerging challenges and opportunities for strengthening privacy practices within academic libraries in the context of evolving digital environments. Results: Findings reveal that while libraries acknowledge the importance of privacy and confidentiality, gaps remain in institutional policies, technical capacity and staff training. The findings suggest that libraries must adopt a multidimensional approach, strengthening cybersecurity, enhancing ethical governance, fostering collaboration and investing in continuous staff development. Conclusion: The study argues for a multidimensional approach that combines robust cybersecurity measures, ethical governance, collaboration and continuous staff development to safeguard patron confidentiality while advancing innovation. Contribution: Libraries must navigate the intersection of technological advancement and ethical responsibility, while ensuring that emerging technologies reinforce, rather than undermine the values of access, equity and privacy.

Investigating the usability, feasibility, and effect of a virtual reality cognitive training system on brain cancer patients with mild cognitive impairment: a quasi-experimental (single-arm) pilot study - Faiola, Anthony; Soroya, Saira (medRxiv, 2026)
Abstract (1) Background Brain cancer is the ninth leading cause of cancer death in the US, with approximately 76,000 newly diagnosed cases annually. Studies show that at time of diagnosis, up to six-months post-treatment, 50%–80% of brain cancer survivors (BCS) report cognitive dysfunction. Mild cognitive impairment (MCI) has gained increasing attention as a persistent disability experienced by up to 75% of all BCS, which affects memory, concentration, executive function, etc. Studies show cognitive training with computerized gaming as improving cognitive function for patients with stroke, dementia, and Parkinson’s. It is of significant clinical interest to develop innovative interventions that reduce MCI. Aim: To improve cognitive performance of BCS suffering with MCI by evaluating the feasibility, acceptability and effect of a Virtual Reality Cognitive Rehabilitation Training (VR-CRT) platform during four weeks of cognitive training (2) Methods We employed a quasi-experimental pretest/posttest non-randomized/non-blinded single-arm design for 4 weeks, with an experimental group (n=6, after attrition) using VR-CRT. Participants were selected based on convenience sampling using the electronic medical record to identify qualified patients, guided by inclusion/exclusion criteria. Feasibility was defined by retention as >80%, with usability testing using the System Usability Scale (SUS) and NASA-TLX surveys. The Hopkins Verbal Learning Test (HVLT), Controlled Oral Word Association (COWA) test, and Trail Making A-B (TM-A/B) test were used to measure cognitive performance, comparing baseline to post week-four. (3) Results The feasibility criteria of >80% was met. All SUS and NASA scores were in the higher index, suggesting a high degree of usability, with low workload demand. For effect, the COWA findings showed a significant improvement (41.38%), with a paired sample T-Test confirming that the participants’ COWA scores improved significantly from pre- to post-intervention ( p = 0.03), indicating enhanced verbal fluency and executive functioning after intervention. HVLT (combined) showed improvements of 18.75% for Form A and 11.32% for Form B, which also showed a significant improvement ( p = .04) in the retention discrimination index from pre- to post-test. The TM-A/B test showed an improvement (25.97%), suggesting that the participants spent less time completing both parts A and B, but was not statistically significant. (4) Conclusion This study fulfilled our aim to demonstrate modest to significant cognitive improvement using VR-CRT with brain cancer patients with MCI. Despite the small sample size, we believe the use of virtual reality will lead to important advances for patients with MCI, particularly the frontal lobe brain region, expressed in executive function.
Keywords: Cognition; Cognitive rehabilitation therapy; Cognitive training; Psychological intervention; Rehabilitation; Test (biology); Usability; Virtual reality; Workload; dept.ils

Investigating the Feasibility, Usability, and Efficacy of a Mobile App to Reduce Anxiety and Depression in Families of Critical Care Cancer Patients: A Quasi-Experimental Pilot Study - Faiola, Anthony; Soroya, Saira; Munker, Reinhold; Hao, Zhonglin; Lambert, Joshua (Healthcare, 2026)
Background: Cancer patients admitted to the bone marrow transplant (BMT) unit face life-threatening medical conditions. Consequently, their family members experience uncertainty, resulting in high levels of anxiety and depression (AD). Limited updates and communication from medical staff exacerbate these emotional burdens. To address these challenges, we developed a mobile health (mHealth) intervention, FamCarePlus, and evaluated its feasibility, usability, and efficacy. We hypothesized that the FamCarePlus application would demonstrate a high degree of feasibility and usability and would reduce AD compared to a control group relying solely on traditional communication through the nurses’ station. Methods: We employed a quasi-experimental pretest/posttest non-randomized, non-blinded self-report design over 3 weeks, with an experimental group (n = 10) using FamCarePlus and a control group (n = 9). We selected participants via convenience sampling using the electronic medical record to identify eligible patients and families, guided by inclusion and exclusion criteria. We used descriptive statistics and the Hospital Anxiety and Depression Scale (HADS) guidelines to analyze the data. Feasibility was defined by a retention rate > 80%, with usability testing using the System Usability Scale (SUS) and NASA Task Load Index (NASA-TLX) surveys. The HADS measured AD, comparing baseline to Week 3. Results: We met our feasibility criteria of >80%. All SUS and NASA scores were in the higher index, suggesting a significant degree of usability and low workload demand on participants. For efficacy, we compared baseline mean scores, with the experimental group reporting lower AD levels at Week 1 (41.9% and 27.8%, respectively) than the control group (55.2% and 34.2%, respectively). From Week 1 to Week 3, the percentage change showed an 8.6% decrease in anxiety in the experimental group, compared to a 12.8% decrease in anxiety in the control group. These results were consistent when analyzed according to HADS guidelines. Conclusions: The findings of this study provide preliminary evidence that the FamCarePlus intervention is feasible and usable, while also demonstrating that its use may be associated with a sustained reduction in AD levels among family members of patients admitted to the BMT unit. These outcomes underscore the potential of digital interventions to address disparities in patient health information access and psychosocial support.
Keywords: Anxiety; Depression (economics); Descriptive statistics; Hospital Anxiety and Depression Scale; System usability scale; Usability; Workload; anxiety; cancer; depression; dept.ils; families; intensive care unit; mHealth